2015
DOI: 10.1099/jmm.0.000076
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular analysis of macrolide-resistant Moraxella catarrhalis clinical isolates in Japan, following emergence of the highly macrolide-resistant strain NSH1 in 2011

Abstract: Although Moraxella catarrhalis is known to be susceptible to macrolides, highly macrolideresistant M. catarrhalis isolates have recently been reported in Japan and China. In this study, we investigated the prevalence of macrolide-resistant M. catarrhalis isolates in Tokyo and Chiba, Japan, and studied the mechanisms underlying their resistance. Specifically, we determined the susceptibility of 593 clinical isolates (collected between December 2011 and May 2014) to erythromycin, using the disk diffusion method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Considering that different non-synonymous mutations may cause the same alternation of amino acid, all the 4770 SNPs analyzed in this study were confirmed after assessment for both synonymous and non-synonymous mutations. In M. catarrhalis , there are four identical copies of rRNA (16S, 23S, and 5S rRNA genes) operons in which the 16S and 23S rRNA genes are interspersed with genes encoding tRNAs for isoleucine and alanine 14 . Among the 4770 SNPs observed to be unique to either susceptible or resistant isolates, 29 were from the rRNA gene, including A2144T, A2330T, and C2480T mutation of 23S rRNA, which were mainly contributed by the resistant isolates ( Table 4 ) as previously noted 7 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering that different non-synonymous mutations may cause the same alternation of amino acid, all the 4770 SNPs analyzed in this study were confirmed after assessment for both synonymous and non-synonymous mutations. In M. catarrhalis , there are four identical copies of rRNA (16S, 23S, and 5S rRNA genes) operons in which the 16S and 23S rRNA genes are interspersed with genes encoding tRNAs for isoleucine and alanine 14 . Among the 4770 SNPs observed to be unique to either susceptible or resistant isolates, 29 were from the rRNA gene, including A2144T, A2330T, and C2480T mutation of 23S rRNA, which were mainly contributed by the resistant isolates ( Table 4 ) as previously noted 7 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, we reported for the first time that ribosomal mutation was crucial for creating macrolide-non-susceptible M. catarrhalis , and that A2330T (position referring to M. catarrhalis 23S rRNA gene, GenBank number NR_103214.1) mutation was related to high-level macrolide-resistance 10 . In the following three years, several studies confirmed that indeed A2330T mutation of the 23S rRNA gene could lead to isolates with high-level macrolide resistance (MIC > 256 g/L) 11 12 13 14 .…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Most M. catarrhalis strains produce β-lactamase; 92% in the PROTEKT study (87). In contrast, M. catarrhalis is almost universally susceptible to azithromycin (87,95,107,108), although macrolide resistance has recently been reported in China (109,110), Japan (111,112), and Pakistan (113). In Australian Indigenous children with bronchiectasis, most M. catarrhalis isolates from the NP (91%) and BAL (100%) were β-lactamase positive; however, azithromycin resistance was not tested (89).…”
Section: Moraxella Catarrhalismentioning
confidence: 99%